The decremental protocol as an alternative protocol to measure maximal oxygen consumption in athletes - Taylor, K.; Seegmiller, J.; Vella, C. (International Journal of Sports Physiology and Performance, 2016)
Purpose: To determine whether a decremental protocol could elicit a higher maximal oxygen consumption (VO2max) than an incremental protocol in trained participants. A secondary aim was to examine whether cardiac-output (Q) and stroke-volume (SV) responses differed between decremental and incremental protocols in this sample.